Living Islamic Law in Indigenous Communities in Indonesia: Integration of Fiqh in the Tradition of Mu’amalah of the Muslim Community of Banjar - Mustofa, Imam; Sauqi, Muhammad; Ambarwati, Diana; Yahya, Alwi (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
The interaction between Islamic law and local wisdom among the Muslim community of Banjar in South Kalimantan reflects the significant dynamics of living Islamic law within the framework of legal pluralism in Indonesia. The mu‘amalah practices developed in this community are not limited to the application of normative fiqh alone, but are brought to life through cultural expressions and oral traditions, such as barelaan, tukar jual, jual lah seadanya, and bawa ja dulu, which serve a dual role as ṣīghat al-‘aqd and as social devices for upholding the principles of voluntariness, openness, honesty, and justice. This study aims to trace the forms, meanings, and mechanisms of integrating the principles of fiqh mu‘āmalah into the customary order, as well as to assess its contribution to the discourse on living law and maqāṣid al-sharī‘ah. A qualitative approach within a phenomenological framework is used. Research data were collected through participatory observation in traditional markets, interviews with local scholars, customary leaders, and traders. The results reveal that local scholars play a strategic role as mediators who interpret and adapt customary practices to align with the principles of Sharia. This process gives rise to a living legal system that is deeply rooted in social legitimacy and endowed with moral authority recognized by the community. From a theoretical perspective, this study broadens the understanding of legal pluralism through a model of reciprocal interaction between Islamic customary law, fiqh mu‘āmalah, and positive law, while enriching the discourse on maqāṣid al-sharī‘ah, particularly in the dimension of ḥifẓ al-māl, which is preventing loss and fostering blessings through social practices based on community trust and ethics.